Cheasy boom - Norizan, Muhammad Syahmi; Norizan, Muhammad Syahmi; Khalil, Siti Nadiah; Saupi, Fifi Syafiqa; Mohd Isa, Farah Wahida; Mazlan, Nursafiqah (2016)
Cheasy Boom is a Bumiputera-owned food-based manufacturer specializing in the manufacturing and production of new frozen meat products, specifically beef and chicken. The core business model leverages freezing as a highly effective preservation method to deliver healthy, high-quality meat with preserved taste, texture, and nutritional value. The company plans to introduce new and innovative flavors to meet high customer demand for frozen meat. Cheasy Boom is strategically located in Bandar Baru Bangi, near Kuala Lumpur, chosen for its potential to facilitate business expansion. The business is scheduled to commence operation on January 8, 2017, a week after its registration on January 1, 2017. Initially, the company will focus on assessing customer acceptance in Bandar Baru Bangi, with the future prospect of expanding the introduction of its frozen meat products to several ways and places based on its performance.